2019
DOI: 10.3389/fgene.2019.00975
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Long Non-Coding RNA and mRNA Expression Profiles in Male and Female Aedes albopictus

Abstract: The Asia tiger mosquito (Aedes albopictus) is an important vector of arboviruses, and females can transmit pathogens such as the dengue, zika, and chikungunya viruses. Understanding sex-related differences in this mosquito is fundamental for vector control. However, there are no reports of systematic characterization of long non-coding RNAs (lncRNAs) in male and female Ae. albopictus. To investigate the roles of coding and non-coding RNAs in both sexes of Ae. albopictus, RNA sequencing was performed on male an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…A recent study in Ae. albopictus identified 2632 novel lncRNAs with a small fraction of these showing male- and female-specific expression patterns [ 85 ]. Work on lncRNAs in mosquitoes remains relatively novel and as a result, nothing is known about the functional consequence of genetic variation in lncRNAs.…”
Section: Long Non-coding Rnasmentioning
confidence: 99%
“…A recent study in Ae. albopictus identified 2632 novel lncRNAs with a small fraction of these showing male- and female-specific expression patterns [ 85 ]. Work on lncRNAs in mosquitoes remains relatively novel and as a result, nothing is known about the functional consequence of genetic variation in lncRNAs.…”
Section: Long Non-coding Rnasmentioning
confidence: 99%
“…albopictus , knowledge on lncRNAs is still limited. Xu et al [ 30 ] reported specifically expressed lncRNAs in males and females. Azlan et al [ 29 ] have identified lncRNAs of Ae .…”
Section: Introductionmentioning
confidence: 99%
“…Noncoding RNAs (ncRNA) are abundant cellular effectors of great prolific functionality ( Eddy 2001 ) and long ncRNA are defined as transcripts, more than 200 nucleotides long, that are produced by RNA polymerase II and are not translated into proteins ( Bonasio and Shiekhattar 2014 ). In Aedes lncRNAs, mainly involved in regulating gene expression, are multifunction with roles including sex differentiation ( Xu et al 2019 ), embryogenesis ( Azlan et al 2019 ), and suppression of viral replication in DENV infected mosquitoes ( Etebari et al 2016 ). Long ncRNAs have also been associated with insect’s response to xenobiotics, with reports of differential lncRNA expression in resistant populations of Plutella xylostella ( Etebari et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%